Diammonium tetraborate dihydrate as hydrolytic by-product of ammonia borane in aqueous alkaline conditions. (20th March 2020) - Valero-Pedraza, María-José; Alligier, Damien; Petit, Eddy; Cot, Didier; Granier, Dominique; Adil, Karim; Yot, Pascal G.; Demirci, Umit B.
Abstract: Ammonia borane NH3 BH3 is able to generate H2 by catalytic hydrolysis at ambient conditions. Such a potential has been much studied but the hydrolysis by-products, i.e. ammonium borates, have been little studied. As such we undertook a systematic work aiming at getting a sound understanding of the borates forming by hydrolysis. Contrary to what is commonly believed, NH3 BH3 (10 M) in aqueous alkaline (pH = 8) solution is not completely stable. Spontaneous hydrolysis takes place, resulting in the formation of by-products and precipitation of borate crystals . This means that long-term storage of concentrated AB solution is not possible. The borate crystals were analyzed with the help of various techniques and was identified as being diammonium tetraborate dihydrate (NH4 )2 B4 O5 (OH)4 ⋅2H2 O (263.39 g mol −1 ). The crystal structure was solved and found to be monoclinic with a space group P 21 . The borate is an analog of borax Na2 B4 O5 (OH)4 ⋅8H2 O. These results, among others, are reported in details hereafter and they are discussed in order to bring elements of response to the questions concerning storage of aqueous NH3 BH3 and recyclability of such a borate. Graphical abstract: Image 1 Highlights: Aqueous alkaline ammonia borane NH3 BH3 (10 M) is not completely stable. Spontaneous hydrolysis takes place, resulting in the formation of borate crystals . Crystals of diammonium tetraborate dihydrate (NH4 )2 B4 O5 (OH)4 ⋅2H2 O form. The crystal structure of this ammonium polyborate is monoclinic (space group P 21 ). Diammonium tetraborate dihydrate is an analog of borax Na2 B4 O5 (OH)4 ⋅8H2 O.